POTENSI VITAMIN B12 SEBAGAI IMUNOMODULATOR TERHADAP TITER ANTIBODI PASCA VAKSINASI HOG CHOLERA - Ervin Elmakhvudz; Diana A Wuri; Meity M. Laut (Jurnal Veteriner Nusantara, 2020)
This study aims to determine the potential of vitamin B12 as an immunomodulator against antibody titers post-vaccination Hog Cholera and leukocyte leukocyte profile of Hog Cholera (HC) vaccination in pigs. The study samples used pigs that had not been vaccinated with a 3 to 12 month age range and were free of parasites. The sample in this study amounted to 32 tails divided into 2 groups namely treatment group (A) and control group (B). The treatment group (A) was given vitamin B12 one day before vaccination while the control group (B) was without vitamin B12.Blood sampling for ELISA assay and leukocyte profile with hematology analyzer on days 0, 5 and 10 days post vaccination. The result of paired t test in treatment group given vitamin B12 showed no significant difference of antibody titer on day 0, day 7 and day 14 (P> 0,005) while in control group showed no difference of antibody titer at Day 0 and day 7 (P>0.005) but on day 14 showed difference of antibody titer (P<0,05). The unpaired t test results to see the difference between the treatment group given vitamin B12 and the control group not given vitamin B12 showed a significant difference (P> 0.005). The unpaired T test results showed no significant difference in the number of leukocytes in both groups (P> 0.005).